The Effect of Story Reading on Incidental Lexical and Grammatical Collocation Learning by Iranian EFL Learners - Naderi, Mina; Barani, Fatemeh (Widya Mandala Catholic University Surabaya, 2020)
The purpose of the present study was to investigate the effect of story reading on incidental lexical and grammatical collocation learning. Moreover, it was an attempt to scrutinize whether there was any significant difference between incidental lexical and grammatical collocation learning. To this end, 36 Iranian EFL learners attending Sadra English Institute in Yasuj participated in the study. They were selected based on the result of quick placement test (QPT) as 28 out of 36 elementary EFL learners. A total of 28 learners were assigned into one experimental group (n=15) and one control group (n=13). The result of the pre-test and post-test analysis using One-Way ANCOVA and MANCOVA revealed the fact that that there was statistically significant increase in collocation knowledge of the learners. In addition, participants performed significantly on grammatical post-test than lexical post-test after the treatment.